Pulsating nanofluids jet impingement cooling of a heated horizontal surface - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2014)
In this study, a numerical study of pulsating rectangular jet with nanofluids is presented. The aim of this work is to numerically investigate the effects of various parameters such as pulsating frequency, Reynolds number, nanoparticle volume fraction on the fluid flow and heat transfer characteristics. The unsteady Navier-Stokes and energy equations are solved with a commercial finite volume based code. It is observed in the steady case, adding nanoparticles increases the peak value of the Nusselt number at the stagnation point and spatial-averaged Nusselt number along the impingement plate. Heat transfer enhancement up to 18.8% is obtained for particle volume fraction of 6% at Reynolds number of 200. In the pulsating flow case, the combined effect of pulsation and inclusion of nanoparticles is not favorable for the augmentation of the stagnation point Nusselt number at Re = 200, phi = 1%, 3% and at Re = 400, phi = 1%, 3% when compared to the steady case. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Nanofluids; Pulsating impinging jet; Heat transfer augmentation